Correction: EDOT-based conjugated polymers accessed via C–H direct arylation for efficient photocatalytic hydrogen production. Issue 8 (11th February 2022) - Tan, Zhi-Rong; Xing, Yu-Qin; Cheng, Jing-Zhao; Zhang, Guang; Shen, Zhao-Qi; Zhang, Yu-Jie; Liao, Guangfu; Chen, Long; Liu, Shi-Yong
Abstract : Correction for 'EDOT-based conjugated polymers accessed via C–H direct arylation for efficient photocatalytic hydrogen production' by Zhi-Rong Tan et al., Chem. Sci., 2022, DOI: ; 10.1039/d1sc05784g .